Penggunaan Metode Suku Kata Untuk Meningkatkan Hasil Belajar Membaca Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas 1 SDN Tlogomas 2 Kota Malang - Firsta Bagus Sugiharto; Chusnul Chotimah; Devi Dominika (Jurnal Lensa Pendas, 2024)
The purpose of study was to describe the level of student learning in reading learning outcomes in Indonesian subjects using the syllable method for first-grade students at SDN Tlogomas 2 Malang City. This study used the Classroom Action Research (PTK) method, which consisted of two cycles, each cycle held 2 class meetings. The approach in this research is descriptive qualitative. The subjects of this study were all first-grade students at SDN Tlogomas 2 Malang City totaly of 20 of them 11 male students and 9 female students. Data collection techniques in this study used observation, interviews, and documentation. The results showed that: (1) the application of the Syllable learning method in cycle 1 meeting 1 presentation 65.00% with sufficient category, the second meeting 75.00% with good category, and in the implementation of cycle II meeting one presentation 85.00% with good category, second meeting 92.05% with very good category. (2) the improvement of Indonesian learning outcomes by using the syllable learning method in Indonesian subjects, cycle 1 meeting one presentation was 50% completeness, with an average score of 67.5%, while in the second meeting, the presentation was 60% completeness, with an average score 69% than in the implementation of cycle II experienced an increase at the first meeting the percentage of completeness was 70% with an average value of 79.5%, and at the second meeting the percentage of completeness was 80% with an average value of 85%. Therefore it can be concluded that using the syllable method in the learning process it can increase the activity and learning outcomes of Indonesian students in class I SDN Tlogomas 2 Malang.